Digital Panopticon Dilemmas: A Study on Contact Tracing Apps Carried Out by the Ministry of Health - Elifnur Terzioğlu (Journal of Economy Culture and Society)
Panopticon, often referred to alongside Michel Foucault and Jeremy Bentham, is a theory that explains the relationship between power and knowledge. Surveillance has gradually become a digital phenomenon as technology has developed, taking on a post-panopticon feature. Thus, it has become possible to monitor the entire flow of information. Although some individuals see this situation as a positive because it saves time and provides digital satisfaction, discussions around it mention that it restricts personal rights and freedoms in most societies. Although individuals voluntarily accept being watched in digital public spaces, they often forget that such surveillance will place them in some extraordinary situations that they might not agree with. During the Covid-19 pandemic, which affected the entire world, governments implemented some digital applications in order to track and manage their population. Through these applications, known as contact tracing systems, there was an attempt to control the spread of the illness. These systems used mobile phone applications to record personal data. This study analyzes 49 countries whose Ministries of Health applied contract tracing applications during the Covid-19 pandemic process through the digital panopticon perception, which would be labeled as classified data according to their democracy indexes.